Diannexin Can Ameliorate Acute Respiratory Distress Syndrome in Rats by Promoting Heme Oxygenase-1 Expression - Ying-nan Ju; Qi-hang Tai; Guang-xiao Xu; Xiao-qing Zhao; Hai-bin Sun; Wei Gao (Mediators of Inflammation)
Background. The recombinant protein diannexin can inhibit platelet-mediated events, which contribute to acute respiratory distress syndrome (ARDS). Here, we investigated the effect of diannexin and its effect on heme oxygenase-1 (HO-1) in ARDS. Methods. A total of 32 rats were randomized into sham, ARDS, diannexin (D), and diannexin+HO-1 inhibitor (DH) groups. Alveolar-capillary permeability was evaluated by testing the partial pressure of oxygen to fraction of inspired oxygen (PaO2/FiO2) ratio, lung wet/dry weight ratio, and protein levels in the lung. Inflammation was assessed by measuring cytokine levels in the bronchial alveolar lavage fluid (BALF) and serum and nuclear factor-κB (NF-κB) in the lung tissue. Inducible nitric oxide synthase (iNOS), malondialdehyde (MDA), and myeloperoxidase (MPO) were measured to evaluate the oxidative stress response. Lung tissue pathology and apoptosis were also evaluated. We measured HO-1 expression in the lung tissue to investigate the effect of diannexin on HO-1 in ARDS. Results. Compared with the ARDS group, diannexin improved PaO2/FiO2, lung wet/dry weight ratio, and protein levels in the BALF and decreased levels of cytokines and NF-κB in the lung and serum. Diannexin inhibited the oxidative stress response and significantly ameliorated pathological lung injury and apoptosis. The partial reversal of diannexin effects by a HO-1 inhibitor suggests that diannexin may promote HO-1 expression to ameliorate ARDS. Conclusions. We showed that diannexin can improve alveolar-capillary permeability, inhibit the oxidative stress response and inflammation, and protect against ARDS-induced lung injury and apoptosis.